Electrochemistry of catalase at a liquid - Zannah, Shaheda; Arrigan, Damien (ELSEVIER SCIENCE SA, 2021)
The electrochemistry of catalase (CAT) was investigated at the interface between two immiscible electrolyte solutions (ITIES) as a step towards its detection. Electrochemistry at the ITIES offers advantages such as the non-redox detection of biomolecules. The electrochemical behaviour of CAT at the ITIES, in a micro-interface array format, displayed a distinct cyclic voltammogram when the aqueous phase pH was lower than the isoelectric point (pI) of CAT. No voltammetric response was observed when the aqueous phase pH > pI of CAT, indicating that neutral or negatively charged CAT has no capability to facilitate anion transfer from the organic phase. Adsorptive stripping voltammetry (AdSV) was assessed for detection of low concentrations at the µITIES array. Application of a positive preconcentration potential for a fixed time enabled interfacial accumulation of CAT as a complex; subsequently, a voltammetric scan to lower potentials desorbed the complex, providing the electroanalytical signal. Assessment of sample matrix effects by examining the electrochemistry of CAT in artificial serum indicated that detection in pH-adjusted samples is feasible. Together, these results demonstrate that CAT is electroactive at the liquid–liquid interface and this may be useful as a strategy to detect and characterize the enzyme in a label-free manner.